The influence of political characteristics on the relationship between family control and firm performance: A meta-analytical approach - Todor Stefan Lohwasser; Felix Hoch (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2019)
This multilevel meta-analytic study, based on 176 studies from 36 countries, examines the impact of political characteristics on the performance of family firms when comparing them to non-family firms (k=311, N=1,598,964). Our findings support the expectation that family firm characteristics are positively related to firm performance. We trace the variance between the studies to differences in certain political characteristics of the firms' countries of origin: government stability, regime stability, regime type and special periods of factionalism. In terms of government and regime stability, we find positive moderating effects on the focal relationship. We further show that periods of factionalism even reverse the superior performance of family firms. While the focal relationship becomes stronger in democracies, the relationship turns negative when looking at anocracies and becomes stronger and positive again considering autocracies. Finally, we reveal that government stability partly mediates the influence of the regime type. Therefore, government stability is a crucial condition for family firms to prosper in any political environment. Our study has several implications for the interplay between family firms and politics: First, the comparative advantage of family firms depends on specific political characteristics. Second, the ability of institutions to provide stability is more important for family firms than the actual institutional setting itself. Third, the impact of a political environment on economic success differs between family firms and nonfamily firms and therefore depends on the structure of the given economy. – – Die vorliegende mehrstufige Metaanalyse, die auf 176 Studien aus 36 Ländern basiert, untersucht die Auswirkungen politischer Einflussfaktoren auf den Erfolg von Familienunternehmen im Vergleich zu Nicht-Familienunternehmen (k=311, N=1.598.964). Unsere Ergebnisse bestätigen die Erwartung, dass die Eigenarten von Familienunternehmen positiv mit deren Unternehmensleistung verbunden sind. Die verbleibende Varianz zwischen den Studien führen wir auf Unterschiede bestimmter politischer Faktoren in den Herkunftsländern der Unternehmen zurück: Regierungsstabilität, Staatsformstabilität, Staatsform und Perioden der Fraktionalisierung. Im Hinblick auf die Stabilität von Regierung und Staatsform finden wir einen positiven moderierenden Einfluss auf die Fokusbeziehung. Darüber hinaus zeigen wir, dass Perioden der Fraktionalisierung den sonst überlegenen Erfolg von Familienunternehmen sogar umkehren. Während die fokale Beziehung in Demokratien stärker wird, wird diese in Anokratien negativ und in Autokratien wieder positiv und stärker. Schließlich zeigen wir, dass die Regierungsstabilität teilweise den Einfluss der Staatsform mediiert. Daher ist die Stabilität der Regierung eine entscheidende Voraussetzung dafür, dass Familienunternehmen in einem politischen Umfeld erfolgreich sein können. Unsere Ergebnisse bringen eine Reihe von Implikationen für das Interaktionsverhalten von Familienunternehmen und Politik mit sich.
Keywords: L33; M21; O16; O57; P51; 650